1984
DOI: 10.1073/pnas.81.2.625
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide-induced contraction and relaxation of the mouse anococcygeus muscle.

Abstract: Isometric tension responses to neuropeptides were recorded from anococcygeus muscles isolated from male mice. This smooth muscle tissue is innervated by inhibitory nonadrenergic, noncholinergic nerves that resemble, ultrastructurally, the peptidergic neurons of the gastrointestinal tract; the physiological function of the anococcygeus is not known. Slow sustained contractions were produced by oxytocin (0.2-20 nM), , and [Arg]-vasotocin (0.4-100 nM); the mouse anococcygeus is, therefore, one of the few example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…In agreement with these data, it has previously been reported that UII inhibits carbachol-induced contraction of the anococcygeous muscle (44) and that dbcAMP and forskolin counteract the contractile response evoked by UII in rat aortic strips (45). UII has also been shown to lower cytoplasmic free Ca 2þ concentration in goby enterocytes (46).…”
Section: Discussionsupporting
confidence: 79%
“…In agreement with these data, it has previously been reported that UII inhibits carbachol-induced contraction of the anococcygeous muscle (44) and that dbcAMP and forskolin counteract the contractile response evoked by UII in rat aortic strips (45). UII has also been shown to lower cytoplasmic free Ca 2þ concentration in goby enterocytes (46).…”
Section: Discussionsupporting
confidence: 79%
“…However, as discussed below, such a hypothesis is not supported by radioligand binding or functional studies performed in both native tissue and recombinant rat/human GPR14 cell lines e.g. non-murine U-II isopeptides are active in mouse non-vascular tissue (goby U-II in the mouse anococcygeus; Gibson et al, 1984), mouse U-II contracts rat aortae and functions as a high a nity ligand at both rat and human GPR14 (Douglas & Aiyar, unpublished observations).…”
Section: Venous Vesselsmentioning
confidence: 99%
“…However, as discussed below, such a hypothesis is not supported by radioligand binding or functional studies performed in both native tissue and recombinant rat/human GPR14 cell lines e.g. non-murine U-II isopeptides are active in mouse non-vascular tissue (goby U-II in the mouse anococcygeus; Gibson et al, 1984), mouse U-II contracts rat aortae and functions as a high a nity ligand at both rat and human GPR14 (Douglas & Aiyar, unpublished observations).To illustrate further the di erences in reactivity between species, U-II was found to exhibit a`coronary-selective' vasoconstrictor pro®le in the dog. This contrasted the vasoconstrictor pro®le of human U-II in the pig where, once again, the spasmogenic pro®le was unique to this species.…”
mentioning
confidence: 99%
“…However, early experiments were carried out with partially purified UII from extracts of fish urophysis; more recently, clear biological activity in mammals has been obtained with a synthetic UII (GUII), having the amino acid sequence of the peptide found in the long-jawed mudsucker, Gillichthys mirabilis (Pearson et al, 1980). An initial observation that GUII produced doserelated relaxations of the mouse anococcygeus muscle (Gibson et al, 1984) prompted further studies of possible actions in mammalian species. In anaesthetized rats, GUII both increased arterial pulse pressure and lowered mean arterial blood pressure (Gibson et al, 1986).…”
Section: Introductionmentioning
confidence: 99%